Carbon Emission Reduction Associated With Utilisation Of Telehealth In Outpatient Clinics In An Australian Quaternary Health Service - Jessica Redmond; Timothy Fazio; Phoebe Darlison; Barbara Ioppi; Monika Page; Katherine A Barraclough; Kudzai Kanhutu; Ben Dunne (ACHSM, 2024)
Objective: To assess the impact of implementing telehealth in outpatient clinics on the carbon emissions associated with the delivery of health care. Design & Setting: Retrospective cohort study in large metropolitan quaternary referral health service from January 2021- December 2022. Participants: All patients who attended an outpatient clinic appointment during the study period, either in-person, via telehealth or via telephone. Main outcome measures: The estimation of carbon emissions in tonnes (t) of CO2-equivalent (CO2-e) associated with in-person and telehealth appointments based on emissions associated with travel, telehealth platform usage and N95 mask usage. Results: There were 571,121 outpatient clinic appointments during the study period. Of the appointments, 251,458 (44%) were conducted remotely, resulting in an estimated reduction in 3,629t of CO2-e emissions in the two-year period. Telehealth consultations in this time contributed 4.5t of CO2-equivalent emissions. The total emission usage of telehealth clinic was only 0.12% of emissions generated from face-to-face clinic appointments. Conclusion: Telehealth offers the opportunity of substantial carbon emissions reduction within the healthcare sector, while also providing cost and time-saving benefits for healthcare services and patients.  Limitations include generalisation of transportation modes and the retrospective nature of the data collection.